Autonomic symptoms are common and are associated with overall symptom burden and disease activity in primary Sjögren's syndrome. Issue 12 (5th May 2012) - Newton, Julia L; Frith, James; Powell, Danielle; Hackett, Kate; Wilton, Katharine; Bowman, Simon; Price, Elizabeth; Pease, Colin; Andrews, Jacqueline; Emery, Paul; Hunter, John; Gupta, Monica; et al.
Abstract : Objectives: To determine the prevalence of autonomic dysfunction (dysautonomia) among patients with primary Sjögren's syndrome (PSS) and the relationships between dysautonomia and other clinical features of PSS. Methods: Multicentre, prospective, cross-sectional study of a UK cohort of 317 patients with clinically well-characterised PSS. Symptoms of autonomic dysfunction were assessed using a validated instrument, the Composite Autonomic Symptom Scale (COMPASS). The data were compared with an age- and sex-matched cohort of 317 community controls. The relationships between symptoms of dysautonomia and various clinical features of PSS were analysed using regression analysis. Results: COMPASS scores were significantly higher in patients with PSS than in age- and sex-matched community controls (median (IQR) 35.5 (20.9–46.0) vs 14.8 (4.4–30.2), p<0.0001). Nearly 55% of patients (vs 20% of community controls, p<0.0001) had a COMPASS score >32.5, a cut-off value indicative of autonomic dysfunction. Furthermore, the COMPASS total score correlated independently with EULAR Sjögren's Syndrome Patient Reported Index (a composite measure of the overall burden of symptoms experienced by patients with PSS) (β=0.38, p<0.001) and disease activity measured using the EULAR Sjögren's Syndrome Disease Activity Index (β=0.13, p<0.009). Conclusions: Autonomic symptoms are common among patients with PSS and may contribute to the overall burden of symptoms and link with systemic disease activity.